Transfer Pricing and Tax Avoidance: A Narrative Review of Global Strategies and Regulatory Challenges - Jakfar; Nuraini, Fariha (Yayasan Sinergi Kawula Muda, 2025)
This narrative review investigates how transfer pricing is strategically utilized by multinational enterprises to facilitate international tax avoidance. The study aims to assess the role of pricing arrangements between related entities in shifting profits to low-tax jurisdictions. Using a comprehensive narrative methodology, literature was gathered from databases such as Scopus and Google Scholar, applying specific keywords and inclusion criteria to identify relevant empirical and conceptual studies. The review identifies a pattern of aggressive transfer pricing behavior, particularly in industries dominated by intangible assets, including technology and pharmaceuticals. These sectors exploit gaps in regulatory frameworks, enabled by the vague implementation of the arm’s length principle. Regulatory interventions such as advance pricing agreements, while theoretically sound, often fail in practice due to institutional weaknesses, especially in developing countries. The discussion further reveals that systemic limitations—such as inadequate legal infrastructure, lack of transparency, and poor data access—contribute significantly to tax base erosion. Findings emphasize the need for harmonized global standards, enhanced international cooperation, and more equitable profit allocation mechanisms. The implications of unregulated transfer pricing extend beyond lost revenue to issues of income inequality and weakened public finance. This study concludes that addressing transfer pricing challenges requires structural reform, institutional strengthening, and sustained global collaboration.